Naoxintong Capsule Inhibits the Development of Cardiovascular Pathological Changes in Bama Minipig Through Improving Gut Microbiota - Zhang, Wei-jian; Su, Wei-wei; Li, Pei-bo; Rao, Hong-yu; Lin, Qing-wei; Zeng, Xuan; Chen, Tao-bin; Yan, Zeng-hao; Liu, Hong; Yao, Hong-liang (Frontiers in Pharmacology, 2019)
Naoxintong capsule (NXT), a Chinese medicine, has performed excellent effects on the prevention and treatment against cardiovascular diseases. NXT is a fine powder mixture without any herb extraction, and there must be lots of ingredients hard to be absorbed. However, little is known about the correlation between the NXT’s cardioprotective effects and gut microbiota. Herein, we report the effect of NXT on the development of cardiovascular diseases and clarify the correlation between NXT’s cardioprotective effects and gut microbiota. In the current study, minipigs were selected and fed with high-fat diet and NXT daily for successive 8 months. During the process, up to 18 biomedical parameters were monthly determined to observe the dynamic changes after NXT treatment. At the end of experimental process, pathological examinations of heart, coronary artery, carotid artery, thoracic aorta, and abdominal aorta were conducted by HE staining and 16SrDNA sequencing, and analyzing of gut microbiota were conducted. Our results showed that NXT’s effects against cardiovascular diseases were through regulating blood lipid profiles, inhibiting vascular inflammation, enhancing antioxidant capacity, and alleviating myocardial injury, without damages on liver and kidney particularly. Concurrently, we also found that long-term administration of NXT increased the diversity of gut microbiota, influenced the microbiome structure and composition stably, and revered the increase of the ratio of the Firmicutes to Bacteroidetes (F/B ratio) in relative abundance. Specifically, our results revealed some key bacterium of Caproiciproducens (enhanced), Sutterella (enhanced), Erysipelotrichaceae (enhanced), and Romboutsia (decreased) that were closely involved in NXT’s effects. Taken together, our study demonstrates that NXT can inhibit the development of cardiovascular diseases by ameliorating high-fat diet–induced metabolic disorders and partly through improving gut microbiota.